Gamma Stirling Engine for a Small Design of Renewable Resource Model - Syed Mohamad Hisyam Wan Dawi; Muhammad Murtadha Othman; Ismail Musirin; Amirul Asyraf Mohd Kamaruzaman; Aainaa Mohd Arriffin; Nur Ashida Salim (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper presents a research on designing a heat engine known as the Stirling engine. The first task is to study on the background of Stirling engine including its robustness, advantages and disadvantages, history and its ability to produce useful energy. Gamma type Stirling engine will be the main focus for this paper. Thus, an effort has been made in determining a suitable formulation that will be used to design a functioning Gamma Stirling engine. This formulation can be divided into several criteria, the Stirling cycle method used to find the p-V diagram of Stirling engine, the 0th order calculation method used as a preliminary system analysis on the efficiency and performance of the engine and lastly, the Schmidt Analysis whereby used in dealing with the design and development of the engine. This formulation is then arranged accordingly into Excel programming software. As for the hardware analysis, it will be on the performance of the Stirling engine model in term of its electrical power production based on different heat source. At the end of this project, it shows that the obtained formulations can be used in designing the Gamma Stirling engine and are capable to produce an output power from the Stirling engine.